Reducing Cognitive Load in Micro-School Systems through Frugal Interaction Design - Muhamad Akda Fathul Barri; Ayu Permata Sari; Suprih Widodo (Journal of Applied Informatics and Computing, 2026)
The rapid digitalization of education marginalizes peri-urban micro-schools, forcing them to adopt complex digital administration tools to maintain institutional legitimacy. However, conventional management systems impose excessive cognitive load on non-technical school stakeholders, leading to low adoption and persistent digital enclaves. This study aims to reduce the extraneous cognitive load of these stakeholders by designing and evaluating a serverless school administration portal based on frugal computing principles. A Targeted Participatory Action Research approach was employed with four core decision-makers at an Islamic micro-school, integrating a web interface directly with habitual messaging applications. Usability was evaluated using task completion metrics and heuristic assessments. The intervention resulted in a complete independent success rate for low-complexity tasks. Furthermore, administrative task completion times decreased dramatically from an average of forty-five seconds to fifteen seconds, with users praising the seamless integration into their daily communication routines. These findings suggest that frugal interaction design and cognitive offloading can effectively bridge the digital divide, providing a sustainable and highly usable administrative model for resource-constrained educational institutions.